Plasma membrane phospholipid signature recruits the plant exocyst complex via the EXO70A1 subunit - Synek, Lukáš; Pleskot, Roman; Sekereš, Juraj; Serrano, Natalia; Vukašinović, Nemanja; Ortmannová, Jitka; Klejchová, Martina; Pejchar, Přemysl; Batystová, Klára; Gutkowska, Malgorzata; Janková-Drdová, Edita; Marković, Vedrana; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Polarized exocytosis is essential for many vital processes in eukaryotic cells, where secretory vesicles are targeted to distinct plasma membrane domains characterized by their specific lipid-protein composition. Heterooctameric protein complex exocyst facilitates the vesicle tethering to a target membrane and is a principal cell polarity regulator in eukaryotes. The architecture and molecular details of plant exocyst and its membrane recruitment have remained elusive. Here, we show that the plant exocyst consists of two modules formed by SEC3-SEC5-SEC6-SEC8 and SEC10-SEC15-EXO70-EXO84 subunits, respectively, documenting the evolutionarily conserved architecture within eukaryotes. In contrast to yeast and mammals, the two modules are linked by a plant-specific SEC3-EXO70 interaction, and plant EXO70 functionally dominates over SEC3 in the exocyst recruitment to the plasma membrane. Using an interdisciplinary approach, we found that the C-terminal part of EXO70A1, the canonical EXO70 isoform in Arabidopsis, is critical for this process. In contrast to yeast and animal cells, the EXO70A1 interaction with the plasma membrane is mediated by multiple anionic phospholipids uniquely contributing to the plant plasma membrane identity. We identified several evolutionary conserved EXO70 lysine residues and experimentally proved their importance for the EXO70A1-phospholipid interactions. Collectively, our work has uncovered plant-specific features of the exocyst complex and emphasized the importance of the specific protein-lipid code for the recruitment of peripheral membrane proteins.
Keywords: buněčná membrána; EXO70A1; proteiny huseníčku; Proteomics; exocyst; Cell Polarity; Arabidopsis Proteins; proteomika; exocytóza; plasma membrane; Arabidopsis; polarita buněk; Phospholipids; Cytoplasm; Exocytosis; cytoplazma; fosfolipidy; Cell Membrane; phospholipids; cell polarity